A phase 1 study to evaluate the safety, tolerability and pharmacokinetics of TAK‐041 in healthy participants and patients with stable schizophrenia. Issue 8 (17th April 2022) - Yin, Wei; Han, David; Khudyakov, Polyna; Behrje, Rhett; Posener, Joel; Laurenza, Antonio; Arkilo, Dimitrios
Abstract : Aims: TAK‐041 (NBI‐1065846), an orally available, investigational, small molecule agonist of GPR139, an orphan G‐protein‐coupled receptor, has shown promise in preclinical studies for the treatment of symptoms associated with schizophrenia. Here, we report the results from a phase 1 study to evaluate the safety, tolerability and pharmacokinetics of TAK‐041 in healthy adults and exploratory efficacy assessment of TAK‐041 as adjunctive therapy to antipsychotics in adults with stable schizophrenia (ClinicalTrials.gov : NCT02748694). Methods: The study comprised 4 parts: parts 1–3 were undertaken in healthy adults and part 4 in patients with stable schizophrenia. Part 1 was a single‐rising‐dose study, part 2 was a multiple‐rising‐dose study that assessed plasma exposure and accumulation, part 3 evaluated the bioavailability of tablet formulation versus oral suspension, and part 4 was a repeat multiple‐dose study in patients with stable schizophrenia. Results: No serious adverse events were reported. TAK‐041 had a nearly linear pharmacokinetics profile, with rapid absorption and long half‐life of 170–302 hours across all doses tested. Bioavailability was similar between the tablet formulation and oral suspension, and no meaningful food effect was detected. Systemic exposure was 22–30% lower for patients with schizophrenia than for healthy volunteers. A potential signal of improvement was detected in the anxiety–depression scale of the Positive and Negative Syndrome Scale ( P  = .0002, not corrected for multiplicity) and the Temporal Experience of Pleasure Scale in patients with schizophrenia. Conclusion: TAK‐041 was generally well tolerated in healthy volunteers and adults with schizophrenia. Further investigation of TAK‐041 in individuals with schizophrenia is supported.